2011
DOI: 10.1111/j.1600-079x.2011.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves d‐galactose‐induced aging effects on behavior, neurogenesis, and lipid peroxidation in the mouse dentate gyrus via increasing pCREB expression

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) has multiple functions. In this study, we investigated the effects of melatonin on memory, cell proliferation, and neuroblast differentiation in the dentate gyrus of a mouse model of D-galactose-induced aging. D-galactose was subcutaneously administered to 7-wk-old mice for 10 wk, and age-matched mice were used as controls. Seven weeks after D-galactose administration, vehicle (water) or melatonin (6 mg/L in water) was administered ad libitum to the mice for 3 wk. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 67 publications
6
83
0
Order By: Relevance
“…[1][2][3] Glycosylation is a non-enzyme reaction among free amino acid groups in collagen, as well as the oxidization induced by oxygen activation gene. However, the glycosylation induced by reaction between reducing sugar and protein is the important factor that causes body aging.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Glycosylation is a non-enzyme reaction among free amino acid groups in collagen, as well as the oxidization induced by oxygen activation gene. However, the glycosylation induced by reaction between reducing sugar and protein is the important factor that causes body aging.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explain the mechanism of D-galactose, many hypotheses have been put forward; one of them is that chronic systemic exposure to D-galactose increases levels of MDA and lipofuscin and also decreases GPx and SOD activities (6,41). In our study, when the Morris water maze test was applied, we observed that long-term administration of D-galactose in mice caused cognitive deficit and showed significant impairment of learning and memory ability.…”
Section: Discussionmentioning
confidence: 67%
“…When it is present at higher levels than normal, it can be converted to galactitol by galactose oxidase, resulting in the generation of oxygen-derived free radicals (6). Chronic systemic exposure to D-galactose induces aging-related changes such as corruption of spatial learning, memory loss, neurodegeneration, and diminishing activities of antioxidant enzymes and increased production of free radicals (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…It also induces the expression of tumor necrosis factor-alpha, interleukin-1b (IL-1b) and IL-6 [13]. DGalactose increases replicative senescence markers p16 expression and telomere shortening but reduces doublecortin (DCX) expression [14]. Therefore, D-galactose continuously stimulates low-grade inflammation, which is associated with the acceleration of aging.…”
Section: D-galactose Induced Alzheimer's Diseasementioning
confidence: 99%